2016
DOI: 10.1007/s10006-016-0607-9
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between lateral displacement of the mandible and scoliosis

Abstract: Lateral displacement of the mandible and scoliosis are related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…Indeed, the difference may be attributable to physiological muscular asymmetry compatible with normal function [2,15,30,31]. Participants showed similar static body postures irrespective of whether their crossbite was on the left or right, similar to the observation that the degree of vertebral deviation correlated with the degree of mandibular deviation only when excluding direction [32]. Although the sample size was sufficient to find body posture differences in subjects with and without UPCB, the small number of participants in the right-side or left-side UPCB group might not have been large enough to find significant comparisons and the findings should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, the difference may be attributable to physiological muscular asymmetry compatible with normal function [2,15,30,31]. Participants showed similar static body postures irrespective of whether their crossbite was on the left or right, similar to the observation that the degree of vertebral deviation correlated with the degree of mandibular deviation only when excluding direction [32]. Although the sample size was sufficient to find body posture differences in subjects with and without UPCB, the small number of participants in the right-side or left-side UPCB group might not have been large enough to find significant comparisons and the findings should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 55%
“…This research was extended in 2017 by Nakashima. The results showed that 11.4% of respondents had a curvature above 10°Cobb and there was a correlation between the deviation of the mandible and scoliosis [59].…”
Section: Methodsmentioning
confidence: 94%
“…However, these relationships in patients with IS are not clear. In the study by Nakashima et al [17], a positive correlation between the Cobb angle and the degree of mandibular deviation was detected, while Ben-Bassat et al [4] found no association between location, side, or severity of scoliosis and the appear-ance or side of the malocclusion. Regarding the association between craniofacial morphology and trunk asymmetry, Zepa et al [25] found that all facial morphologic variables were almost similar in patients with left-sided and right-sided scoliosis.…”
Section: ______________________________mentioning
confidence: 93%
“…Both fluctuating asymmetry and the presence of increased directional asymmetry were observed in patients affected by IS [9]. Many researchers have also suggested a relationship between a postural deformity of the trunk, such as IS and asymmetric orthodontic conditions [4], [17], [20], [22]. According to a systematic review published in 2011 [21], there is plausible evidence for an increased prevalence of unilateral Angle Class II malocclusions, lateral crossbite, midline deviation as well as reduced range of lateral movements in patients affected by scoliosis.…”
Section: ______________________________mentioning
confidence: 99%